(untitled) (Research, Society and Development, 2023)
Edentulism is still a challenge in the daily life of dentists and the elderly population is the most affected one. There are many related reasons for it, from socioeconomic levels to the lack of basic oral health instructions. Dental prostheses, either fixed or removable, are the way to provide the patient a better quality of life, by restoring their masticatory, phonetic and psychological functions. Oral rehabilitation is one of the important aspects for improving the patient’s quality of life, but it’s not as important as the instructions for the correct use of dental prostheses with the purpose and intention of avoiding the emergence of oral lesions. This work aims to describe the main oral injuries related to the inappropriate usage of dental prostheses and their risks to the patient’s quality of life, as a source of relevant information for the dental surgeon. It is a narrative review study of the investigated literature, which pointed out that the main injuries related to the use of prostheses were: candidiasis, prosthetic stomatitis, traumatic ulcers, angular cheilitis and inflammatory fibrous hyperplasia.